Florística e caracterização dos campos rupestres sobre canga na Serra da Calçada, Minas Gerais, Brasil1 - Viana, Pedro Lage; Lombardi, Julio Antonio [UNESP] (Instituto de Pesquisas Jardim Botânico do Rio de Janeiro, 2007)
Ferrugineous rocky grasslands are a peculiar environment frequently found at the Quadrilátero Ferrifero region, Minas Gerais State. The vegetation, associated to hematitic outcrops, presents physiological and morphological adaptations, as well as high levels of endemism. A floristic survey, restricted to phanerogames, and a descriptive characterization of the ferrugineous rocky grasslands of Serra da Calçada are presented. Studies of specimens collected from July 2001 and August 2002 were complemented by exame of collections deposited at BHCB Herbarium. A total of 358 species distributed in 70 families were registred. The richest families were Poaceae (43 spp.), Asteraceae (42 spp.), Fabaceae and Myrtaceae (21 spp. each), Melastomataceae and Orchidaceae (18 spp. each). Most of the species (210 spp.) occur on grassy fields (or canga nodular), while 153 occur on rocky fields (or canga couraçada), 93 on forest islands and 47 on anthropized areas. Ferrugineus grasslands is under threatened due to mining exploration and urban development, therefore urgent conservation measures are essential to protect threatened plant species.

Os campos rupestres sobre canga são um ambiente peculiar e freqüente na região do Quadrilátrero Ferrífero, Minas Gerais. Sua vegetação, associada a afloramentos hematíticos, apresenta uma série de adaptações morfológicas e fiosiológicas, assim como alto grau de endemismo. Foi realizado um leventamento florístico, restrito às fanerógamas, e uma caracterização descritiva dos campos rupestres sobre canga na Serra da Calçada. Para tal, realizaram-se campanhas de campo mensais, entre junho de 2001 e agosto de 2002, e foram analisados exemplares depositados no herbário BHCB. O levantamento contou com 358 espécies distribuídas em 70 famílias, sendo as famílias mais ricas Poaceae (43 spp.), Asteraceae (42 spp.), Fabaceae e Myrtaceae (21 spp. cada), Melastomataceae e Orchidaceae (18 spp. cada). A maioria das espécies (210 spp.) ocorre em canga nodular, 153 em canga couraçada, 93 em capões de mata e 47 em áreas antropizadas. O alto grau de ameaça a que este ambiente está submetido e a presença expressiva de espécies ameaçadas de extinção implicam na necessidade urgente de preservação de áreas que compreendem campos rupestres sobre canga.
Floristics and characterization of the ferrugineous rocky grasslands at Serra da Calçada, Minas Gerais state, Brazil
Keywords: flora; rocky grasslands; canga; ferrugineous grasslands; Quadrilátero Ferrífero; flora; campos rupestres; canga; campos ferruginosos; Quadrilátero Ferrífero